Transformasi Peran Konselor BKI dalam Membangun Ekosistem Pesantren Ramah Inklusi dan Anti-Kekerasan: Integrasi Konseling Humanistik dan Wacana Islam Progresif. - Shafiyudin , Ibnu Rafid; Haqiqi , Fatkhiyya Nur (Jurnal Bimbingan dan Konseling Islam, 2025)
The phenomenon of violence in educational institutions, including Islamic boarding schools (pesantren), remains a serious issue that threatens human dignity and the quality of education. This study aims to explore the strategic role of Islamic Guidance and Counseling (BKI) counselors in building inclusive and violence-free pesantren through the integration of humanistic counseling and progressive Islamic values. Using a qualitative library research approach, this study constructs a conceptual framework that combines Carl Rogers’ humanistic principles empathy, unconditional positive regard, and congruence with progressive Islamic theology that emphasizes justice, equality, and liberation from discrimination. The findings reveal that BKI counselors are not only problem solvers at the individual level but also cultural change agents who are capable of challenging hierarchical relations and structural violence in pesantren. The integration of humanistic counseling with progressive Islam provides space for a more humane, egalitarian, and contextual education, while simultaneously strengthening the child-friendly pesantren movement. This study contributes theoretically to the development of a transformative Islamic counseling framework and practically provides a foundation for pesantren administrators in designing fair and anti-violence policies.